Ancient Christian commentary on Scripture ; NT v.Ib - Simonetti, Manlio (Downers Grove, IL IVP, 2002)
Contents : v. Ib : Matthew 14-28. Includes bibliographical references and indexes
Keywords: Bible. N.T. Matthew XIV-XXVIII -- commentaries